The Psychometric Properties of the Norwegian version of Preschool Anxiety Scale – Revised (PAS-R) - Backer-Grøndahl, Agathe; Helland, Siri Saugestad (PsykTestBarn, 2020)
Description: The Preschool Anxiety Scale – Revised (PAS-R; Edwards, Rapee, Kennedy, & Spence, 2010) is an instrument measuring a broad spectrum of anxiety symptoms in preschool children. The PAS-R consists of 28 items measuring social anxiety, generalized anxiety, separation anxiety, and specific phobias. It was translated to Norwegian by Ørbeck, Eyre, and Kristensen in 2013, and is free to use by clinicians and researchers. Literature Search: A systematic literature search for Norwegian, Danish, and Swedish studies reporting the psychometric properties of the PAS-R resulted in two Master theses. These reports were based on cross sectional data from a normal population of preschool children in a pilot study (N = 37), and the main study (N = 260) from “Tuning in to Kids” at the University of Oslo, Norway. Psychometrics: The mean values for the PAS-R in these two studies were presented with different scaling than the original, so the values were recalculated to allow for comparison with international data. The results indicated good reliability (internal consistency) for the total scale. The mean PAS-R total scale values in the Norwegian sample were lower than the original sample but were higher than the mean values found in an Icelandic sample. Psychometric data for the subscales were not reported in the two Norwegian studies. Conclusion: We have limited data regarding the psychometric properties of the Norwegian version of the PAS-R. Despite this, we would encourage the use of the PAS-R in Norwegian studies, as this is one of few instruments measuring different anxiety dimensions in children. Further results in Norwegian samples are needed to document the psychometric properties of the Norwegian version.